IMPACT OF VERBAL AND NON-VERBAL COMMUNICATION ON MARITAL STABILITY OF COUPLES IN UKUM LOCAL GOVERNMENT AREA OF BENUE STATE: COUNSELLING INTERVENTION. - Akume, Gabriel Terzungwe; Saatan, Ruth Movihinze (Sokoto Educational Review, 2013)
This study investigated the impact of verbal and non-verbal communication on marital stability of couples in Ukum Local Government Area of Benue State. The variables in this study examined were verbal and non-verbal communication. Two research questions and two hypotheses (at 0.5 level of significance) were formulated to guide the study. The- survey design was adopted using 384 respondents randomly selected from a population of 70,360 married couples in the study area. A self-structured, Marital Communication and Stability Inventory (MCSl) was used as an instrument to collect data for the study. The data obtained was analyzed using frequencies, percentages and chi-square statistics. It was found that verbal and non-verbal communication has a significant impact on marital stability of couples in the area of study. The study, therefore, recommended among others that couples should learn to adopt effective marital communication in a marriage relationship for peaceful coexistence. Counsellors should start early by organizing social clubs in primary and post-primary schools to help students learn the rudiments of interpersonal communication skills.